Prophetic pastoral leadership: The Adelaide archdiocesan pastoral team, 1986-2001 [Book Review] - McEvoy, James Gerard (The Australasian Catholic record, 2018)
Review(s) of: Prophetic pastoral leadership: The Adelaide archdiocesan pastoral team, 1986-2001, by Paul K. Hawkes, (Calwell, ACT: Inspiring, 2018), pp. 138; paperback, AU$23.00;1 Kindle, US$7.29.